Profiling the effects of physicochemical indexes on the microbial diversity and its aroma substances in pit mud. (1st December 2020) - Zhang, M.; Wu, X.; Mu, D.; Yang, W.; Jiang, S.; Sun, W.; Shen, Y.; Cai, J.; Zheng, Z.; Jiang, S.; Li, X.
Abstract: Microbial diversity of pit mud (PM) plays a significant role in Baijiu's flavour. Here we explored the microbial community structures and aroma substances of Wenwang Winery with high‐throughput sequencing coupling with headspace solid‐phase microextraction‐gas chromatography‐mass spectrometry. We discovered that the odorant was mainly derived from 14 aroma compounds because of their OAVs ≥ 1 (OAV, the ratio of substance concentration to aroma threshold; s, on behalf of the plural), such as ethyl hexanoate (2438), ethyl octanoate (975), caproic acid (52) and etc. Moreover we also revealed that Lactobacillaceae (97·08%) was the mainly bacterial microbial community in 2‐year‐old PM, companied by the primarily fungi including Aspergillaceae (55·45%), Unclassified Ascomycota (11·13%) and Dipodascaceae (5·72%). Compared with the 2‐year‐old PM, bacterial floras in 20‐year‐old PM and 30‐year‐old PM were more abundant (i.e. Dysgonomonadaceae, Clostridium and Synerggstaceas ), while no fungi were detected. Besides, the physicochemical analysis showed that the content of Lactobacillaceae was inversely associated with moisture, pH and ammonia nitrogen. By further Spearman's correlation coefficient analysis, we verified that the content of Lactobacillaceae was positively correlated with ethyl hexanoate, while negatively correlated with ethyl octanoate and caproic acid. Meanwhile, ethyl octanoate and caproic acid were positively correlated with most flora including Ruminococcaceae, Dysgonomonadaceae and Clostridiacea, which were related to physicochemical indexes. This work demonstrates promise for adjusting the physicochemical indexes of PM to affect the micro‐organisms and aroma, which may provide a reference for the production of high‐quality Baijiu.